Epstein-Barr virus in non-Hodgkin lymphoma of the tonsil in Indonesian patients (Faculty of Medicine Universitas Indonesia, 2001)
Twenty cases of tonsillar non-Hodgkin lymphoma seen at the Department of Anatomic Pathology, Faculty of Medicine, University of Indonesia during 1995-1997 were studied clinicopathologically. The specimens were analysed for routine histopathology, in situ hybridization and immunohistochemistry. The lymphoma was found mostly in the 7th decade, the median age was 57.5 year. Male to female ratio was 1:1. The hostological types were 70% of intermediate grade and 30% of high grade of malignancy. All of the lymphomas were B cell lymphomas. EBER and LMP1 were not expressed in all cases. (Med J Indones 2001; 10: 69-72) Keywords : tonsil lymphoma, clinicopathologic profile, immunopheno type, ebv